Rapid Determination of 9 Tyrosine Kinase Inhibitors for the Treatment of Hepatocellular Carcinoma in Human Plasma by QuEChERS-UPLC-MS/MS - Jiang, Wen; Zhao, Tingting; Zhen, Xiaolan; Jin, Chengcheng; Li, Hui; Ha, Jing (Frontiers in Pharmacology, 2022)
A reliable and rapid method employing QuEChERS (Quick, Easy, Cheap, Effective, Rugged, and Safe) pretreatment coupled with ultra-performance liquid chromatography–tandem mass spectrometry (UPLC–MS/MS) was successfully developed and validated for the analysis of 9 tyrosine kinase inhibitors (TKIs) in human plasma. Biological sample was extracted with acetonitrile and salted out with 350 mg of anhydrous magnesium sulfate (MgSO4), followed by the addition of 40 mg of ethyl enediamine-N-propylsilane (PSA) adsorbents for purification. All analytes and internal standards (IS) were separated on the Hypersil GOLD VANQUISH (2.1 × 100 mm, 1.9 μm) column using the mobile phases composed of acetonitrile (phase A) and 0.1% formic acid in water (phase B) within 8.0 min. Detection was performed using selection reaction monitoring (SRM) in the positive ion electrospray mode. Lenvatinib, sorafenib, cabozantinib, apatinib, gefitinib, regorafenib, and anlotinib rendered good linearity over the range of 0.1–10 ng/mL and 1–100 ng/mL for tivantinib and galunisertib. All linear correlation coefficients for all standard curves were ≥0.9966. The limits of detection (LOD) and the limits of quantitation (LOQ) ranged from 0.003 to 0.11 ng/mL and 0.01 to 0.37 ng/mL, respectively. The method was deemed satisfactory with an accuracy between -7.34% and 6.64%, selectivity, matrix effect (ME) of 90.48–107.77%, recovery, and stability. The proposed method is simple, efficient, reliable, and applicable for the detection of TKIs in human plasma samples as well as to provide reference for the clinical adjustment of drug administration regimen by monitoring the drug concentrations in the plasma of patients.